2-Methyl-1,10b-dihydro-5H-pyrazolo[1,5-c][1,3]benzoxazin-5-one - Kettmann, Viktor (International Union of Crystallography, 2009)
In the title compound, C(11)H(10)N(2)O(2), a potential inhibitor of the cyclooxygenase-2 isoenzyme, the pyrazoline ring exists in a flat-envelope conformation while the puckering of the central oxazine ring is more severe. As a result, the molecule as a whole is non-planar. The formal sp (3) pyrazoline N atom is sp (2) hybridized, with the lone-pair electrons delocalized through conjugation with the carbonyl group rather than the double bond of the pyrazoline ring.